National Identity Crisis of Indonesian Education in the Global Era - Jumari, Jumari; Juliangkary, Eliska; Pujilestari, Pujilestari; Sriartha, I Putu (Al-Hayat: Journal of Islamic Education, 2024)
This study examines the national identity crisis in Indonesian education globally. This type of research is literature with a qualitative approach. Data collection by reconstructing data from books, archives, magazines, documents, journals, documentation, newspapers, etc. Using the philosophical hermeneutic analysis approach of Hans-Georg Gadamer through the stages of interpretation, holistic, and heuristic. This study shows that education is needed to strengthen national identity in the vortex of social change. Globalization is like a "three-edged sword," namely it can weaken or even eliminate a culture (transcendence), can help revive a culture (transference), and can cause a mixture of cultures (transformation) between globalization and local culture. In addition, the factors causing the national identity crisis based on a global perspective from a sociological vision are specific culture (web culture), antisocial nature, and low criticality of adolescents in facing the development of technological culture. From an anthropological perspective, namely the hegemony of global culture by international powers, the weak resilience of society in facing the onslaught of global culture, the noble values ​​of culture are starting to erode and may even disappear at some point, and modern culture is replacing old traditions. This research is limited to a narrow-scope analysis of the national identity crisis, while there is still a need for other essential aspects that need further study. Education should not only examine the intellectual side but there is a need for a balance of science and knowledge so that the output is not only intelligent in intellectual terms but also has value, one of which is national identity and love for one's products and culture.